Hubungan Antara Dukungan Sosial Teman Sebaya dengan Body Image pada Remaja di Mts Al-Uswah Bergas Kabupaten Semarang: The Relationship Between Peer Social Support and Body Image in Adolescents at Mts Al-Uswah Bergas Semarang Regency - Oktaviani, Ismi; Pranoto, Heni Hirawati (Journal of Holistics and Health Sciences, 2025)
Adolescence is a transitional period from childhood to adulthood. Teenagers often struggle to accept the physical changes that occur during puberty. They may feel embarrassed, anxious, and confused by these changes. A preliminary study found that 3 out of 5 teenagers were dissatisfied with their body shape and lacked self-confidence, 6 out of 10 teenagers had acne, and 4 out of 5 teenagers practiced unhealthy dieting. Body image is an evaluation of one's personal characteristics based on emotional experiences. One factor that influences adolescent body image is peer social support. This study aims to determine the relationship between peer social support and body image among adolescents at MTS Al-Uswah. This research is a descriptive quantitative study with a cross-sectional approach. The population consisted of 58 eighth-grade students at MTS Al-Uswah, selected using proportional random sampling. The instrument used was a questionnaire. Data were analyzed using the chi-square test. The study found no significant relationship between peer social support and body image among adolescents at MTS Al-Uswah, with a result of 0.412 (p>0.05). The majority of eighth-grade adolescents at MTS Al-Uswah received supportive peer social support (51.7%) regarding changes during adolescence. Most of them had a positive body image (55.2%), indicating acceptance and comfort with themselves. There was no relationship between peer social support and body image among adolescents at MTS Al-Uswah, with a p-value of 0.412 > α 0.05. It is suggested that future researchers explore additional variables that influence body image. ABSTRAK Masa remaja adalah masa peralihan dari kanak-kanak menuju dewasa. Remaja sering kali kesulitan dalam menerima perubahan fisik yang terjadi selama pubertas. Mereka merasa malu, cemas, dan bingung dengan perubahan tersebut. Hasil studi pendahuluan ditemukan 3 dari 5 remaja tidak puas dengan bentuk tubuhnya dan tidak percaya diri, ada 6 dari 10 remaja memiliki jerawat, serta 4 dari 5 remaja diet tidak sehat. Body image adalah penilaian karakteristik diri berdasarkan pengalaman perasaan yang telah dialaminya. Faktor yang mempengaruhi body image remaja seperti dukungan sosial teman sebaya. Penelitian ini bertujuan untuk mengetahui hubungan antara dukungan sosial teman sebaya dengan body image pada remaja di MTS Al-Uswah. Penelitian ini adalah deskriptif kuantitatif dengan pendekatan cross sectional. Populasi yaitu remaja kelas VIII di MTS Al–Uswah sejumlah 58 responden dengan teknik pengambilan sampel proportional random sampling. Instrumen menggunakan kuesioner. Data dianalisis menggunakan uji chi square. Hasil penelitian yaitu tidak ada hubungan antara dukungan sosial teman sebaya dengan body image pada remaja di MTS Al-Uswah dengan hasil 0,412(p>0,05). Sebagian besar remaja kelas VIII di MTS Al–Uswah memiliki dukungan sosial teman sebaya mendukung sebanyak 51,7% terhadap perubahan pada masa remaja. Sebagian besar remaja kelas VIII di MTS Al–Uswah memiliki body image positif sebanyak 55,2% menerima dengan baik dan merasa nyaman dengan dirinya. Tidak ada hubungan antara dukungan sosial teman sebaya dengan body image pada remaja di MTS Al-Uswah, nilai p-value 0,412>α0,05. Saran untuk peneliti selanjutnya memperluas variabel yang mempengaruhi body image.